Research Paper: Evaluation of the Effects of Two Types of Foot Rockers on the Temporal-Spatial Gait Parameters in Diabetic Patients - Zeinab Rezaeian; Mohammad Taghi Karimi; Arezoo Eshraghi; Niloofar Fereshtenejad (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective Foot ulcer is one of the main challenges of diabetic patients influencing their abilities to stand and walk. Various methods have been suggested to decrease the loads applied to the foot in this group of patients; most methods were not deemed successful and could only be used temporarily. Rocker shoes are recommended for foot ulcer treatment. Based on the available literature, it is still controversial whether or not the forces applied to the foot differ between diabetic and normal subjects.  Moreover, it is not well understood which kind of rocker (heel or toe rocker) is more successful in decreasing the applied forces to the foot. Therefore, this study aimed to compare the loads applied on the foot in diabetic subjects and normal subjects and to determine the influence of rockers on the load of foot. The main hypothesis associated with this study was that heel and toe rockers had similar effects on the force applied on the foot in diabetic subjects.  Materials & Methods In this interventional, and quasi-experimental study, 20 healthy and 20 diabetic subjects were recruited. The sample size was determined based on the average number of the subjects in the previous similar studies. The diabetic subjects were selected from the patients referred to foot clinics in Rehabilitation School of Isfahan University of Medical Sciences. A qualysis motion analysis system with a Kistler force plate (50×60 cm) was used to record the temporal-spatial gait parameters and forces applied on the leg during walking. The subjects were asked to walk with a comfortable speed along a level surface in a gait lab.  The parameters such as temporal-spatial gait parameters, peaks of ground reaction forces, and force-time integral were used for analysis. The difference between the mean values of the parameters and between the subjects’ effects were evaluated by use analysis of variance with repeated measures test. The statistical analysis was done by SPSS17 and with significant level of 0.05. Results There was a significant difference between normal and diabetic foot subjects regarding cadence, stride length, and percentage of stance phase (P < 0.05). Although the walking speed of diabetic subjects was less than that of normal subjects, the difference was not significant (P > 0.06). There was a significant difference between the peak of the forces (anteroposterior [fy1, fy2], medio lateral [fx], and vertical [fz1, fz2, fz3]) applied on the leg in normal and diabetic foot. The type of rocker did not affect the spatiotemporal gait parameters (P < 0.05), while exhibited significant effect on the peak anteroposterior forces applied to the leg (P < 0.04). The mean value of the force-time integral of vertical component of ground reaction force varied based on the side and group (P < 0.04). Conclusion The results of this study showed that the force-time integral of vertical component of the ground reaction force increased significantly in subjects with diabetes, which is the main cause of foot ulcers. Although, heel and toe rockers did not influence the force applied to the foot or the force-time integral, it is recommended to use rocker shoes with wide base of support to increase the dynamic stability while decreasing the foot pressure. The main limitation is that the immediate effect of use of rocker was studies in this study . It is recommended to check the effect of rockers interventions after a certain period of their use.